Study guides

☆☆

Q: How do you prove that sinθ plus cosθ2 plus sinθ-cosθ2 equals 2?

Write your answer...

Submit

Still have questions?

Related questions

cos2 + cos2tan2 = cos2 + cos2*sin2/cos2 = cos2 + sin2 which is identically equal to 1. So the solution is all angles.

Use these identities: sin2(x) + cos2(x) = 1, and tan(x) = sin(x)/cos(x) For clarity, the functions are written here without their arguments (the "of x" part). (1 - sin2) = cos2 (1 + tan2) = (1 + sin2/cos2) = (cos2+sin2) / cos2 = 1/cos2 Multiply them: (cos2) times (1/cos2) = 1'QED'

You can't it equals 2. You can't it equals 2.

There is not cos2 button on a TI-83 plus. You will need to enter the cosine function and then square it. (Press the x2 button to get the squared function.) To type cos2(90) on a TI-83 plus, for example, type: cos(90)2

No you can not prove that 9 +10 = 21.

Using x instead of theta, cos2x/cosec2x + cos4x = cos2x*sin2x + cos4x = cos2x*(sin2x + cos2x) = cos2x*1 = cos2x

To determine what negative sine squared plus cosine squared is equal to, start with the primary trigonometric identity, which is based on the pythagorean theorem...sin2(theta) + cos2(theta) = 1... and then solve for the question...cos2(theta) = 1 - sin2(theta)2 cos2(theta) = 1 - sin2(theta) + cos2(theta)2 cos2(theta) - 1 = - sin2(theta) + cos2(theta)

Using a calculator

Original Equationsec2(x) = 1 + tan2(x)Leave the left side assec2(x) and for the proof, try to make the right side equal the left side.We know tan = sin/cos1 + tan2(x) = 1 + sin2(x)/cos2(x)Rewrite the 1 in terms of cos2(x)1 + sin2(x)/cos2(x) = cos2(x)/cos2(x) + sin2(x)/cos2(x)Simplify, now that the denominators have the same termscos2(x)/cos2(x) + sin2(x)/cos2(x) = [ cos2(x) + sin2(x) ] / cos2(x)Use the trig. identity: cos2(x) + sin2(x) = 1[ cos2(x) + sin2(x) ] / cos2(x) = 1 / cos2(x)Remember 1/cosine is equal to secant.\1 / cos2(x) = sec2(x)Recall, the left side the equation was: sec2(x)The right side (we just solved for is): sec2(x)sec2(x) = sec2(x)Left side = right side, Q.E.D.

Because there is no way to define the divisors, the equations cannot be evaluated.

prove PE=IE+SE

Yes

People also asked